KONSEP WAHDATUL ADYAN IBNU ‘ARABI DALAM PENYELESAIAN KONFLIK AGAMA - Dzulkifli M. Mooduto (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
Religion conflict does not only happen because of exclusivism, but also intolerant between religion adherents. However, in the other hand, reconciliation efforts to avoid it have been carried out. One way to resolve this conflict is looking at the consept of Wahdatul Adyan by Ibnu Arabi. This paper aims to explain Ibnu Arabi thoughts for the purposes of resolving inter religion conflict.